1970
DOI: 10.1139/p70-379
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray yields from the reaction D(p, γ)3He at low energies

Abstract: Total cross sections and measurements of the small isotropic component of the γ-ray yield from the reaction D(p, γ)3He have been determined in the energy range from 57 to 1100 KeV using gas and deuterated polyethylene targets. The results are compared with some theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…The target gas composition is monitored with a mass spectrometer Q200, where the analyzed gas is reduced via a special pressure converter DWl Fig. This reaction proceeds [37][38][39][40] by the direct capture mechanism and represents a case similar to the 3He(~, y)7Be reaction. The pressure reduction in the jet target system along the accelerator beam axis (Fig.…”
Section: Jet-quality For 7-ray Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The target gas composition is monitored with a mass spectrometer Q200, where the analyzed gas is reduced via a special pressure converter DWl Fig. This reaction proceeds [37][38][39][40] by the direct capture mechanism and represents a case similar to the 3He(~, y)7Be reaction. The pressure reduction in the jet target system along the accelerator beam axis (Fig.…”
Section: Jet-quality For 7-ray Spectroscopymentioning
confidence: 99%
“…4.1.1) the 3He(~, 7)TBe cross sections were measured relative to the well-known DC cross sections for the reactions D(p, y)3He [37][38][39][40] and ~60(p,~)lTF [14,57,58]. 4.1.1) the 3He(~, 7)TBe cross sections were measured relative to the well-known DC cross sections for the reactions D(p, y)3He [37][38][39][40] and ~60(p,~)lTF [14,57,58].…”
Section: I2 Cross Section Relative To Non-resonant Capture Reactimentioning
confidence: 99%
“…Two previous studies of the H(p, y) He reaction have been made in the energy region of interest (E"~80 keV) [3,4]. Our rationale for restudying this reaction comes from the fact that the existing data set below 50 keV (Griffiths et al.…”
mentioning
confidence: 99%
“…There are several data sets for this reaction in the BBN window: however, some of these measurements need detailed consideration. It has been suggested that the Griffiths'63 [5] and Bailey'70 [6] experiments used incorrect stopping powers and, consequently, their low energy behaviour is 15% too high. The Schmid'97 [7] data set suffer from poor energy resolution, with typical uncertainties greater than 10%.…”
Section: Existing Experimental Datamentioning
confidence: 99%